Pengembangan Media Pop-up Book Berbasis Multimedia Terhadap Hasil Belajar Tematik Siswa Kelas IV Sekolah Dasar - Fadhilah, Nurul; Sutopo, Yeri; Sunarso, Ali (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2022)
This study aims to analyze the feasibility and influence of multimedia-based pop-up book media on the thematic learning outcomes of fourth-grade elementary school students—research method using Research and Development (R&D) ADDIE design. The research subjects were 59 students. Data collection techniques used validation sheets, test sheets, documentation, observations and interviews. The data analysis technique used a feasibility test and an independent sample T-test. The results showed that the pop-up book media feasibility test based on multimedia is in the very feasible category, and the thematic learning outcomes of the experimental class students were more effective than the control class. The study results concluded that there was a significant effect of the use of multimedia-based pop-up book media on thematic learning outcomes. Students seem enthusiastic about participating in learning during the learning process, and it is found that there are social skills and student creativity in group discussions. Based on the research results, it is expected that researchers/teachers can innovate multimedia-based learning media to become more interactive so that learning becomes interesting for students.